Lack of clean water access in rural schools in Northern Argentina: Air humidity water collection and dust filtration technology to obtain clean water - Cornet, Tiago; Strack Garcilazo, Juan Pablo (My University, 2023)
Abstract— The water scarcity problem is critical in rural schools in northern Argentina, where geographical challenges, limited financial resources and alternative water sources contribute to the lack of water access. The United Nations’ Sustainable Development Goals #4 and #6 encompass the problem stated in this paper, and it is a central problem to the 2030 Agenda. Once the drivers of the problem are understood two options will be presented to obtain clean water: Fresh Water Ecco System and the P&G Purifier Packets. Finally, pros and cons of each innovation will be discussed. It is expected that this work might provide insight into this topic that needs urgent attention, and also raise awareness about deficiencies that there exist in some parts of Argentina, and how these affect the education and social development of the inhabitants.

Resumen— El problema de la escasez de agua es crítico en las escuelas rurales del norte de Argentina, donde los desafíos geográficos, los recursos financieros limitados y las fuentes alternativas de agua contribuyen a la falta de acceso. Los Objetivos de Desarrollo Sostenible de las Naciones Unidas #4 y #6 abarcan el problema mencionado en este trabajo el cual es un problema central en la Agenda 2030. Una vez que se comprendan los impulsores del problema, se presentarán dos opciones para obtener agua potable: un sistema llamado Fresh Water Ecco System y un producto purificador de agua de P&G. Finalmente, se discutirán los pros y contras de cada innovación. Se espera que este trabajo provea información sobre este tema, el cual requiere atención urgente y que además, genere conciencia sobre las deficiencias que existen en algunas partes de Argentina y cómo afectan a la educación y al desarrollo social de los habitantes.
Keywords: water harvesting; water management; water scarcity; recolección de agua; tratamiento de agua; escasez de agua